Representações das relações de gênero nas práticas do sistema judiciário: o caso das ações cíveis de alimentos em Bragança-PA (1969-2013) - ALVES, Alessandra Brito (2022)
This research aims to analyze how the judicial system in Bragança-PA represents the places of men and women in their legal practices in the Civil Actions for Food that were brought in Bragança-PA with Law 5.478 / 68, from 1969 to the year 2013. The development of the Food Actions and their legal results support the objective of this work, as well as the analysis of the criteria used by the Bragantino judicial system to stipulate the values of food in benefits for minors and women, and what are the justifications used by the parents and ex-spouse for not paying for this maintenance. This research has a qualitative approach, with analysis of judicial documents, supported by theoretical references that show that justice, through its agents, propagates the dominant ideology, reinforcing gender asymmetries and hierarchies.